Fine mapping of the human MHC class II region within chromosome band 6p21 and evaluation of probe ordering using interphase fluorescence in situ hybridization. - Senger, G; Ragoussis, I; Trowsdale, J; Sheer, D (1993)
Eight previously well-characterized and mapped probes derived from the human major histocompatibility complex (MHC) class II region were used to investigate the advantages and limitations of fluorescence in situ hybridization (FISH) techniques for fine mapping. The class II region of the MHC was localized within subband 6p21.31 by in situ hybridization on metaphase chromosomes that were banded by immunofluorescence staining with an antibody against 5-bromodeoxyuridine (BrdU). Ordering of probes that were separated by up to 900 kb was achieved by simultaneous hybridization of two or three probes on interphase nuclei. Three-color FISH proved to be an excellent method for ordering of probes within distances of 200-1,000 kb. Under certain conditions, closer probes could be ordered by comparing measured distances between their hybridization signals in interphase nuclei. A linear correlation between measured interphase distances and kilobase distances was observed up to 500 kb. With increasing distances, the measurements become more inaccurate due to chromatin folding.